In vitro evaluation of antioxidant, probiotic, and antiproliferative activity of Ganoderma lucidum-extracted polysaccharides for the prevention of complication associated with gastrointestinal inflammatory diseases - Mina Zangeneh; Hossein Derakhshankhah; Masoud Modarresi; Babak Haghshenas; Zohre Foroozanfar; Zhila Izadi (Heliyon)
Inflammatory bowel diseases (IBD), including ulcerative colitis and Crohn's disease, are associated with increased oxidative stress, chronic inflammation, and in some cases, abnormal cell proliferation, which can lead to serious complications such as cancer. Identifying natural compounds with antioxidant, anti-inflammatory, and probiotic properties could be an effective strategy in the prevention and management of these diseases. Medicinal mushrooms have been widely used in Asian countries for decades as natural remedies for improving health conditions and treating various diseases. In this research, we studied the potential of antioxidant, probiotic, and antiproliferative activity of Ganoderma lucidum polysaccharides (GLPs) as a potential supplementary candidate. The structure of the extracted polysaccharides from Ganoderma lucidum was studied by FT-IR and NMR. The antioxidant effect of GLPs was evaluated by DPPH and Fe3+ reduction. A comprehensive study was conducted on the capabilities of GLPs to induce in vitro apoptosis on Caco-2, PC3, and epithelial cells. Finally, the probiotic activity of these polysaccharides was examined in vitro by determining the changes in optical density (OD).Our results showed that GLPs have a significant dose-dependent inhibitory effect against free radicals, so the antioxidant effect of these compounds is emphasized. In addition, GLPs regardless of their molecular weight can be considered as effective agents to improve the tolerance of Lactobacillus as an important probiotic. Also, the growth inhibitory activity of these compounds on cancer cells can be a suitable preventive candidate to reduce the risk of cancer in patients suffering from inflammatory bowel diseases.Based on these data, the findings of this study showed that GLP can be a complementary candidate in the prevention and management of inflammatory diseases of the gastrointestinal tract and its related complications such as oxidative stress and abnormal cell proliferation.